Trading for bailouts - Toni Ahnert; Caio Machado; Ana Elisa Gonçalves Pereira (Bank of Canada, 2020)
Government interventions such as bailouts are often implemented in times of high uncertainty. Policymakers may therefore rely on information from financial markets to guide their decisions. We propose a model in which a policymaker learns from market activity and where market participants have high stakes in the intervention. We study how the strategic behavior of informed traders affects market informativeness, the probability and efficiency of bailouts, and stock prices. We apply the model to study the liquidity support of distressed banks and derive implications for market informativeness and policy design. Commitment to a minimum liquidity support can increase market informativeness and welfare.
Keywords: D83; G12; G14; G18; 330; Financial institutions; Financial markets; Financial system regulation and policies; Lenderof last resort